2022
DOI: 10.3390/s22020649
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Silent Speech Interfaces Based on Frequency-Modulated Continuous-Wave Radar

Abstract: Speech is our most natural and efficient form of communication and offers a strong potential to improve how we interact with machines. However, speech communication can sometimes be limited by environmental (e.g., ambient noise), contextual (e.g., need for privacy), or health conditions (e.g., laryngectomy), preventing the consideration of audible speech. In this regard, silent speech interfaces (SSI) have been proposed as an alternative, considering technologies that do not require the production of acoustic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…The result of 95% approves that the mouth motion produces informative signals for UWB sensing 7 . FMCW radar is also an optional choice which has been proven in the result of the paper 8 . The mentioned work adopts point clouds of human mouth while speaking as data feature for classification work of 13 words with 4 speakers.…”
Section: Methodsmentioning
confidence: 97%
“…The result of 95% approves that the mouth motion produces informative signals for UWB sensing 7 . FMCW radar is also an optional choice which has been proven in the result of the paper 8 . The mentioned work adopts point clouds of human mouth while speaking as data feature for classification work of 13 words with 4 speakers.…”
Section: Methodsmentioning
confidence: 97%
“…FMCW radar utilizes continuous wave signals, whereas IR-UWB radar employs pulse signals for its functionality. Thus, the signal processing algorithm used in the FMCW radar-based SSR studies of [29], [30], and [31] cannot be directly applied to our IR-UWB radar-based SSR study.…”
Section: Principles Of Ir-uwb Radar-based Ssrmentioning
confidence: 99%
“…As indicated in Table 2, with the same vowel corpus as that used in our study, the method proposed in [28] achieved an accuracy of only 51.59%, whereas our method (FERASEC + DNN-HMM) achieved a significantly higher accuracy of 86.47%. Ferreira et al [30] reported an accuracy of 88.3% for a 13-word European Portuguese classification task with four participants using an FMCW radar.…”
Section: Performance Comparison With Other Contactless Radar-based Ss...mentioning
confidence: 99%
See 2 more Smart Citations